Eighteen new species and fifteen new records of the genus Torodora Meyrick (Lepidoptera: Lecithoceridae) from China - Yu, Shuai; Zhu, Yanmei; Wang, Shuxia (Zootaxa, 2022)
Eighteen new species of the genus Torodora Meyrick, 1894 from China are described: T. acuminata sp. nov., T. atomata sp. nov., T. canaliculata sp. nov., T. costatiprolata sp. nov., T. dentisaccula sp. nov., T. gemella sp. nov., T. gongshanensis sp. nov., T. longicornis sp. nov., T. obliqua sp. nov., T. parisortilega sp. nov., T. procerispinata sp. nov., T. reniformis sp. nov., T. spectabilis sp. nov., T. stilliformis sp. nov., T. strigulosa sp. nov., T. ventrimaculata sp. nov., T. xizangensis sp. nov. and T. zhejiangensis sp. nov.; 15 species are newly recorded for China. Images of adults and genitalia for all newly described species and a checklist of the Chinese Torodora species are given.